Enhancement of Arachidonic Acid Production by A Newly Isolated Diplosphaera sp. Associated with Bryophyte - Kunriya, Piyawan; Yongmanitchai, Wichien; Lertwattanasakul, Noppon; Kato, Yasuo; Nomura, Taiji; Chonudomkul, Duenrut (Trends in Sciences, 2025)
Arachidonic acid (ARA) is an essential omega-6 polyunsaturated fatty acid with significant roles in nervous system development and various physiological processes. While ARA production from freshwater microalgae has been limited, this study aimed to optimize cultivation conditions for ARA production in Diplosphaera sp. DMKU4.11.2, a newly isolated strain from a bryophyte in Thailand. Among 6 tested media, BG11 demonstrated the highest ARA production. Further optimization of the BG11 medium involved adjusting factors such as the nitrogen source, nitrogen concentration, phosphorus ratio, phosphorus level and sodium chloride supplementation. The optimal conditions were determined to be BG11 medium containing 0.75 g/L sodium nitrate and potassium phosphate at a 1:1 ratio, with 3.50 mg P/L. Under these conditions, Diplosphaera sp. DMKU4.11.2 produced the highest ARA yield of 115.31 ± 2.03 mg/g dry cell weight (DCW), with an ARA production rate of 3.23 ± 0.12 mg/L/day. Supplementing the medium with 50 mM sodium chloride further enhanced ARA content to 9.57 ± 1.67 % of total fatty acids (TFAs) and increased biomass production to 0.36 ± 0.00 g/L. Culturing in the optimized BG11 medium resulted in a 1.24-fold increase in growth and a 3.95-fold increase in ARA content compared to the standard BG11 medium. In conclusion, this study highlights the potential of Diplosphaera sp. DMKU4.11.2 as a sustainable source for ARA production, with opportunities to enhance productivity for industrial and health-related applications. HIGHLIGHTS The freshwater microalga Diplosphaera DMKU4.11.2, newly isolated from a bryophyte in Thailand, was identified for its potential in producing arachidonic acid (ARA). BG11 medium demonstrated the highest ARA production among tested media. Cultivation in modified BG11 resulted in a 1.24-fold increase in biomass and a 3.95-fold increase in ARA content, compared to cultivation in standard BG11. GRAPHICAL ABSTRACT